Dancing on the edge of silence : Steps towards articulating the experience of childhood rape - Downing, Brenda Joy (2008)
The experience and aftermath of male sexual violence is a lived reality for many girls and women. This qualitative study explores the subjective experience of childhood rape and its long-term impact focusing in particular on the implications of the silencing that continues to surround what is a deeply-felt and traumatic experience with profound life-altering consequences. The study thematically and theoretically reads the subjective experience of childhood rape within current feminist understandings of rape as a crime of violence and form of social control through the use of evocative autoethnographic writing and an exegesis